ECONOMIC LOSS OF ONLINE MOTORCYCLE TAXI DRIVERS DUE TO ACCOUNT CLONING: A CASE STUDY OF TOMOHON CITY : Kerugian Ekonomi Pengemudi Ojek Online Akibat Kloning Akun: Studi Kasus Kota Tomohon - Lenda Lumentah; Jola Silvana Kalangi; Julita Inggrinne Nelwan; Royke Max Suot; Rieneke Kalalo; Sjerly Maria Lumi; Welky Karauwan; Lalira, James (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the economic losses suffered by online motorcycle taxi drivers in Tomohon City due to account cloning, a growing form of digital exploitation in Indonesia’s gig economy. The research examines financial, operational, and psychological impacts, evaluates platform security measures, and assesses the erosion of consumer trust. A mixed-methods approach was employed, combining quantitative surveys with 50 drivers and qualitative in-depth interviews with drivers, customers, and platform representatives. Data were collected through structured questionnaires, participatory observation, and thematic analysis. Quantitative data were analyzed using descriptive statistics to measure income decline and additional costs, while qualitative data were interpreted through thematic content analysis to understand lived experiences and systemic vulnerabilities.Findings reveal that 44% of income reduction is directly linked to account-related disruptions, with affected drivers losing between IDR 500,000 and 1,000,000. Additional recovery costs further strain their financial stability. Psychologically, 76% reported moderate to high anxiety, and 64% stated that the threat of cloning negatively affects work motivation. Consumer trust is compromised, as 80% of drivers acknowledge reputational damage due to service inconsistencies caused by cloned accounts. Despite high awareness of cloning (82%), only 40% implement preventive measures, and 70% perceive platform responses as inadequate. The discussion highlights that account cloning is a systemic issue rooted in weak platform governance and low digital literacy. The absence of compensation mechanisms exacerbates worker vulnerability. This study recommends mandatory implementation of advanced security protocols, integrated digital literacy programs, and a formal gig worker protection framework including rapid reporting and financial compensation. These measures are essential for building a fairer and more sustainable digital transportation ecosystem.